Study of hygienic hand disinfection of staff and dental students at the Medical University - Plovdiv - Atanaska Petrova Petrova; Velina Stoeva; Hristiana Batselova (National Scientific Medical Center, 2024)
Introduction: Transient microbial flora on the hands of medical personnel is a prerequisite for healthcare-associated infections. Unlike permanent this micro flora can be removed by washing and disinfection. The hands of the dental staff are factor number one in the transfer of microorganisms: from patient to patient as well as on objects from the dental environment. The aim of the present study was to microbiologically examine hand washes of 5th year dental students and medical staff before starting work with a patient in order to evaluate the quality of hygienic disinfection performed. Methodology: The hands of a total of 115 doctors and students from the Faculty of Dental Medicine of the Medical University of Plovdiv were wiped with a sterile swab after treatment with a disinfectant. Isolates were identified to species using Vitek MS and MALDI-TOF technology. Results: Coagulase-negative staphylococci with a microbial number of 103-104 were found to have the highest microbial count (70%). 9% of the samples with coagulase-negative staphylococci had microbial count ≥105. The most common isolates detected were: Staphylococcus hominis, Staphylococcus epidermidis and Micrococcus luteus. Conclusion: The presence of coagulase-negative staphylococci in a high microbial count, enterococci and representatives of Bacillus simplex is undesirable, especially in immunosuppressed patients. These results highlight the need to increase knowledge about hand disinfection and its actual application before working with a patient.